-6+4(-2x-5)=-25-9x

Simple and best practice solution for -6+4(-2x-5)=-25-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+4(-2x-5)=-25-9x equation:


Simplifying
-6 + 4(-2x + -5) = -25 + -9x

Reorder the terms:
-6 + 4(-5 + -2x) = -25 + -9x
-6 + (-5 * 4 + -2x * 4) = -25 + -9x
-6 + (-20 + -8x) = -25 + -9x

Combine like terms: -6 + -20 = -26
-26 + -8x = -25 + -9x

Solving
-26 + -8x = -25 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-26 + -8x + 9x = -25 + -9x + 9x

Combine like terms: -8x + 9x = 1x
-26 + 1x = -25 + -9x + 9x

Combine like terms: -9x + 9x = 0
-26 + 1x = -25 + 0
-26 + 1x = -25

Add '26' to each side of the equation.
-26 + 26 + 1x = -25 + 26

Combine like terms: -26 + 26 = 0
0 + 1x = -25 + 26
1x = -25 + 26

Combine like terms: -25 + 26 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| 12.8=x-3.5 | | -7b+3=-6b+4 | | 4x^3-44x=0 | | 2x+7=15-9x | | (5x+3)-x=31 | | -15+3(p-2)=5(2p-3)+8 | | -6x+4(2x-5)=-25-9x | | x/3+15=25 | | (ln)y=9t+2 | | 6x+4x=15 | | 25q+18=100-13q+70 | | 2(2v-3)=2v-5 | | logy=9t+12 | | (x+4)/2=7 | | 2-x=-10 | | 2x^2-5x+55=0 | | lny=9t+12 | | 1/4(2x-14)=4 | | 3(X-4)=20 | | 7-m=5+3 | | 1.5x+1=4 | | 7a+3=8-2a | | 0=4x^2-8x+15 | | (3x+6z)3= | | 6x-10=4x+6 | | 49p^3q-25pq^3=0 | | x+3+5x= | | 2y^2+48y+288=0 | | 15-5t=0 | | 5(x-2)+4(3x+x)=83 | | 9x^2+24x+20=0 | | 3y+11=17 |

Equations solver categories